2010
DOI: 10.1128/jcm.00644-10
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Characterization of Enterotoxigenic Escherichia coli Strains Isolated from Peruvian Children

Abstract: Enterotoxigenic Escherichia coli (ETEC) is a major cause of childhood diarrhea. The present study sought to determine the prevalence and distribution of toxin types, colonization factors (CFs), and antimicrobial susceptibility of ETEC strains isolated from Peruvian children. We analyzed ETEC strains isolated from Peruvian children between 2 and 24 months of age in a passive surveillance study. Five E. coli colonies per patient were studied by multiplex real-time PCR to identify ETEC virulence factors. ETEC-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
29
4
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 30 publications
(30 reference statements)
14
29
4
2
Order By: Relevance
“…We identified ETEC in all age groups except in the 37-48 months group, from which no ETEC strain was isolated. The highest ETEC prevalence in our results was observed among children 49-60 months of age, which is similar to the findings of Riveria et al and conforms with the commonly reported more frequently isolation of ETEC from children > 12 months of age than from children < 12 months of age [39]. This corroborates the fact that ETEC strains might be considerably important enteropathogens, especially in pediatric patients in the 0-5 years age group [40].…”
Section: Discussionsupporting
confidence: 82%
“…We identified ETEC in all age groups except in the 37-48 months group, from which no ETEC strain was isolated. The highest ETEC prevalence in our results was observed among children 49-60 months of age, which is similar to the findings of Riveria et al and conforms with the commonly reported more frequently isolation of ETEC from children > 12 months of age than from children < 12 months of age [39]. This corroborates the fact that ETEC strains might be considerably important enteropathogens, especially in pediatric patients in the 0-5 years age group [40].…”
Section: Discussionsupporting
confidence: 82%
“…However, variations in toxin profiles were observed from year to year. Different studies in Latin America have shown differences in the predominant toxin type; for instance, LT/ST ETEC strains were found to be most prevalent in Peru (19), ST-only ETEC strains in Brazil (20) and LT ETEC strains in Argentina (23), in Nicaragua (21), and in a previous report from Bolivia (16). A similar trend has been observed in Bangladesh, where different toxin profiles have predominated over the years (24)(25)(26).…”
Section: Discussionsupporting
confidence: 57%
“…In Bolivia, a previous report showed that ETEC strains expressing LT CS17 constituted the most common pathotype isolated between 2002 to 2005, but those strains were from different clonal origins (31). In recent studies in Peru, CS6-and CS12-positive strains (19), and, in Brazil, CFA/I-and CS14-expressing ETEC strains (20) were the predominant pathotypes. Several review articles have indicated that a limited number of CFs, including CFA/I, CS1 to -6, and, more recently, CS7, CS14, and CS17, are repeatedly identified as the most common CFs for ETEC, suggesting a continuous circulation of similar strains among populations (2,6,32).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increase in the incidence of ETEC-mediated diarrheal disease, considerable attention has been paid to the development of simple, sensitive, and less expensive molecular methods for rapid identification of the pathogen. Currently, CFAs are detected by conventional PCR assay, replacing the conventional immunological tests (7,12,13,16,17).The CS6 operon is composed of four genes, cssA, cssB, cssC, and cssD. The structural genes of CS6 are cssA and cssB, which exhibit variation in different CS6-expressing ETEC isolates (16,20).…”
mentioning
confidence: 99%
“…Due to the increase in the incidence of ETEC-mediated diarrheal disease, considerable attention has been paid to the development of simple, sensitive, and less expensive molecular methods for rapid identification of the pathogen. Currently, CFAs are detected by conventional PCR assay, replacing the conventional immunological tests (7,12,13,16,17).…”
mentioning
confidence: 99%